2016
DOI: 10.1007/s10337-016-3104-2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Glabridin, (−)-α-Bisabolol, and Ascorbyl Tetraisopalmitate in Whitening Cosmetic Creams Using HPLC-PAD

Abstract: α-bisabolol, and ascorbyl tetraisopalmitate, respectively. The calibration curves showed good linearity with determination coefficients (R 2 ) ≥ 0.999. The mean recoveries were ranged between 89.8 and 103.9 % with relative standard deviations (RSDs) <5 %. The intra-and inter-day precision was <2 %. The limits of detection (LODs) were 0.03, 0.4, and 4.02 μg mL −1 for glabridin, (−)-α-bisabolol, and ascorbyl tetraisopalmitate, respectively. The method was successfully applied for monitoring 11 market samples, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Even though EA is a compound widely used in topical products (Jeon et al, 2016, Silva et al, 2019), surprisingly, its physicochemical properties have not been reported to date. Additionally, the skin permeation profile of EA has not been investigated nor have the effects of different vehicles on skin uptake of EA been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Even though EA is a compound widely used in topical products (Jeon et al, 2016, Silva et al, 2019), surprisingly, its physicochemical properties have not been reported to date. Additionally, the skin permeation profile of EA has not been investigated nor have the effects of different vehicles on skin uptake of EA been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that the anti-inflammatory effect of α-bisabolol might be linked to the inhibition of some proteins, such as inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) and the transcription factors NF-kB, ERK and p38 [ 10 ]. Recently, new findings have shown that α-bisabolol is involved in the inhibition of the cAMP response element (CRE) by reducing intracellular cAMP levels in melanocyte cells [ 11 ]; however, it has also been demonstrated that α-bisabolol could act as an inhibitor of voltage-dependent calcium channels by promoting the inhibition of smooth muscle contractions in isolated rat arteries, as reported by [ 12 ]. To date, no studies have been conducted on the relaxing, immunomodulatory and anti-inflammatory properties of α-bisabolol in the pregnant human uterus.…”
Section: Introductionmentioning
confidence: 99%
“…For certain businesses, prohibited substances may be added to enhance the effectiveness of short-term cosmetics. Chemical analysis techniques for cosmetic products that have been reported include thin layer chromatography, [4][5][6][7] capillary electrophoresis, 8,9 gas chromatography with flame ionization detection 10,11 or coupled with various types of mass spectrometers, 12 and high-performance liquid chromatography using ultraviolet, [13][14][15][16][17][18][19] electrochemical detection, [20][21][22] or coupled with various types of mass spectrometers. [23][24][25][26][27][28][29] Sample pretreatment for these methods usually requires multiple steps to complete.…”
Section: Introductionmentioning
confidence: 99%